Effect of air pollution on lung function of road side hawkers - Kumar, Pawan; Gupta, Sonisha; Asthana, Smita (Indian Journal of Community Health, 2020)
Background: There is increasing concern of ambient air pollution as a global threat to humans. The most prominent effect of air pollution is on lung function. The air pollution causes decline in lung function amongst high exposure populations. There are some most vulnerable groups who are chronically exposed to ambient air pollution like traffic policemen, roadside hawkers, Banjara community in India, E-Rickshaw drivers etc. Methods: A cross sectional study was conducted in East Delhi, India. Spirometry was done for roadside hawkers having high exposure to ambient Air pollution and working daily for 6-8 hours for the last more than 3 years. The low exposure group was taken from personnel working inside offices. The spirometry parameters of both the groups were compared. Student ‘T’ test was applied for statistical analysis with the help of SPSS software. Results: Comparison of FVC, FEV1 and FEV1/FVC ratio among two groups revealed lower values for the high exposure group which was statistically significant. Among high exposure group the mixed pattern of ventilation defect was observed. Among low exposure group normal pattern of lung function was observed. Conclusion: Roadside hawkers are a vulnerable group to ambient air pollution resulting in their lower values of lung function parameters with resultant mixed ventilator defect and consequently high risk for development of respiratory diseases in the future.